Korelasi Motivasi Belajar Terhadap Prestasi Belajar Siswa Kelas X Mata Pelajaran PAI Di SMKN 13 Malang Subhan Adi Santoso - Subhan Adi Santoso; Devi Ari Setiawan; Muhammad Nur Hamdi; Mahludhotul Faroha (STIT Muhammadiyah Paciran, 2022)
: Learning is an activity that proceeds and is a very fundamental element in the implementation of each type and level of education. This means that the success or failure of the achievement of the educational objectives depends very much on the learning process that students experience when they are at school or in their home or family. Based on the background of the above problem, then the formulation of the problem as follows: What is the learning motivation of students of class X Subject PAI In SMKN 13 Malang and Is there a correlation of learning motivation with student achievement class X Subject PAI In SMKN 13 Malang. The method used in data collection is descriptive method. While the approach taken is a quantitative approach. Data collection in this study includes literature study and field study. The implementation of this field study involves observation techniques, interviews, and using data collection instruments in the form of questionnaires. Based on the results of correlation analysis obtained 0,538. In order for this number to be meaningful, it needs to be interpreted so as to give an explanation of the correlation between learning motivation and student achievement, that is by consulting through the value of r on the product momenttable, either with a significance level of 5% or 1%. For more details will be interpreted r o and r t (table) as follows. At the level of significance of 5% with the number of respondents (N) = 22 obtained r t = 0.423, while r o = 0.538. Thus r o is greater than r t or in other words r o> r t. This means indicating a significant or positive correlation between the two variables. At the level of significance of 1% with the number of respondents (N) = 22 obtained r t = 0.537, while r o = 0.538. Thus r o is greater than r t or in other words r o> r t. This means indicating a significant or positive correlation between the two variables. So the hypothesis examined that